Leadership : theory, application, & skill development - Lussier, Robert N.; Achua, Christopher F., 1961- (Los Angeles : SAGE, 2023)
"Packed with self-assessments, applications, and exercises, Leadership: Theory, Application, and Skill Development 7e offers a highly practical introduction to leadership theories and concepts. Bestselling author Robert N. Lussier and Christopher F. Achua provide integrated coverage of global, ethical, and social issues help prepare students for a wide range of leadership situations and challenges"--
Revised edition of the authors' Leadership, [2016]
Includes bibliographical references and index.
Keywords: Leadership; Teams in the workplace